Harnessing the Power of Administrative Data to Create a Provincial-Level Child Heath Profile and Birth Cohort in New Brunswick (NB) and Prince Edward Island (PEI) - Tranchant, Carole; Montelpare, William; Bélanger, Mathieu; Miedema, Baukje; Sénéchal, Martin (International Journal of Population Data Science, 2018)
Introduction Early-life prevention of chronic diseases is crucial to a healthy adulthood. However, evidence is often lacking to assess the effectiveness of early intervention programs, partly because of failure to make use of existing data. This project aims to capitalize on existing administrative data in two provinces to address this gap. Objectives and Approach To identify and evaluate selected administrative databases (AD) from NB and PEI to create an intra-provincial Child Health Profile (CHP) and establish the foundation for a population-based birth cohort database in each province using existing administrative data. Integrated knowledge translation (iKT) was implemented to facilitate the continuous involvement of knowledge users and stakeholders, including provincial government managers/decision-makers, data custodians, health practitioners, parents and community organizations. Consultations were held to identify the AD of interest and develop a roadmap for the CHP. For each dataset, a list and description of data and analytical variables was produced and data access requested. Results Not all AD identified are equally complete and accessible to researchers. Data access, preparation and linkage are challenging but feasible. This process was facilitated by iKT, which also contributes to capacity building. Several AD, mainly healthcare AD, including the Healthy Toddler Assessment and NutriSTEP, are currently accessible. An analytic framework was developed for pulling the data together and planning their analyses to produce the CHP. Based on the data currently accessible, the first CHP will focus on data at birth and at 18 months. Other databases (e.g., preschooler assessments) may be included subsequently. Work is underway to create workable datasets from which the CHP and roadmap for the birth cohort are being developed. This approach is scalable and can be extended to other jurisdictions. Conclusion/Implications Select AD in NB and PEI are rich resources for establishing a comprehensive CHP and population-based birth cohort database in each province. These new tools will enable various stakeholders to monitor and report on child health over the long term, and to evaluate current practices and future health interventions.